Comparação entre as concentrações de tetraciclina no plasma, líquido sinovial e leite de vacas acometidas de dermatite digital papilomatosa, submetidas à administração intravenosa regional - Rodrigues, Celso Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
The majority of lameness in cattle originates in the foot. Currently, there are only limited treatment options available and source of significant economic loss also. The antimicrobial therapy should be based in bacterial sensitivity and pharmacokinetics features. The antimicrobial agent should have a broad antibacterial spectrum and achieve high concentrations in all tissues infected, particularly bone and synovial fluid. Intravenous regional antibiosis consists in place a rubber tourniquet around distal limb during up to 60 minutes and injects a water-soluble antibiotic into a digital vein. This method has been used to improve podal disease treatment. The purpose of this study was compare single-dose concentrations of crystalline tetracycline chloridrate, injected intravenous (IV) and intravenous regional (IVR) in bovine plasma, synovial fluid and milk from dairy cattle. Twelve milk production dairy cattle were used with various stages of digital dermatitis. Cows were randomly assign two groups of six animals. Group 1 will inject a single-dose of 10 mg/Kg crystalline tetracycline chloridrate IV and Group 2 with 1000 mg of crystalline tetracycline chloridrate IVR. Blood, synovial fluid and milk samples were take from jugular vein, left tarsal joint and mammary gland respectively at 0 (control), 22 minutes, 45 minutes, 1 hour and 22 minutes, 2, 3, 4, 6, 8, 12, 24, 48, 72, 96 e 120 hours late injections. Tetracycline concentrations in samples were determined by high-performance liquid chromatography (HPLC). Mean values tetracyclines plasma concentration in Group 1 were higher than Group 2. Synovial fluid and milk tetracycline concentration showed opposite comportment. Group 2 tetracycline concentration in synovial fluid was higher than Minimal Inhibitory Concentration (MIC) during 24 hours for the most frequent bacterias, which cause claw disease. Mean milk antibiotic concentration in Group 2 indicated that would be necessary withdraw up to 96 hours.

A maioria das claudicações na espécie bovina é originária de doenças podais com opções de tratamento limitadas e constituem-se em um dos mais importantes problemas que acomete a espécie. A escolha do medicamento deve estar baseada na sua sensibilidade bacteriana e características farmacocinéticas, devendo recair sobre substância de amplo espectro de ação, capaz de atingir elevadas concentrações nos diferentes tecidos envolvidos na infecção podal. A antibiose intravenosa regional (AIVR), consiste na administração de antimicrobiano hidrossolúvel, após a aplicação de torniquete na extremidade do membro. O objetivo deste trabalho foi comparar as concentrações e farmacocinética do cloridrato de tetraciclina cristalina, no plasma, líqüido sinovial e leite de vacas acometidas de dermatite digital papilomatosa, administrado em dose única, pela via intravenosa jugular ou pela via intravenosa regional. Foram utilizadas 12 vacas em lactação acometidas de dermatite digital papilomatosa. Posteriormente os animais foram divididos aleatoriamente em dois grupos de seis, onde o Grupo 1 recebeu dose única de 10 mg/kg de cloridrato de tetraciclina cristalina intravenosa jugular e o Grupo 2 recebeu 1000 mg de cloridrato de tetraciclina cristalina intravenosa regional. As amostras de sangue da veia jugular, líqüido sinovial do tarso e leite de todos os animais foram colhidas imediatamente antes... .
Keywords: Bovino - Doenças - Tratamento